Squatters in Wilayah Persekutuan Kuala Lumpur: eviction procedures and challenges / 'Azi 'Azlin Zulkifli …[et al.] - Zulkifli, 'Azi 'Azlin; Zamri, Izzat Asyraf; Zulkiflee, Fadzlin; Mohd Zain, Muhammad Arif (2010)
53 years of freedom from colonization does not make Malaysia stops from trembling with the issue of squatters. With a focus on Wilayah Persekutuan Kuala Lumpur, this research looks at the eviction procedure of squatters run by Dewan Bandaraya Kuala Lumpur as well as some problems which restrain the eviction procedure from being successful. This research describes the power of the local council and challenges they need to overcome in handling squatters' matters. However, it is not clear that the current law could help effectively in achieving the mission of Zero Squatters 2010. It further suggests that the law exist should be clarified in order to curb the loopholes and to be complied with the practice of the eviction procedure itself.